1993
DOI: 10.1111/j.1471-4159.1993.tb03176.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐Methyl‐d‐Aspartate Releases γ‐Aminobutyric Acid from Rat Striatum In Vivo: A Microdialysis Study Using a Novel Preloading Method

Abstract: In vivo microdialysis was used in conjunction with a novel dual-label preloading method to monitor changes in extracellular levels of y-aminobutyric acid (GABA) and glutamate due to N-methyl-D-aspartate (NMDA) infusion in the striaturn of conscious, unrestrained rats.[I4C]GABA and [3H]glutamate were applied in the dialysis stream for a preloading period of 30 min, after which dialysis perfusion was continued for up to 6 h and dialysate samples were collected for analysis by liquid scintillation spectrometry. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 21 publications
3
22
0
Order By: Relevance
“…In striatum, local infusion of the Glu agonist N-methyl-D-aspartate (NMDA) increases extracellular DA (Keefe et al, 1992;Moran et al, 1993;Kendrick et al, 1996), GABA (Moran et al, 1993;Young and Bradford, 1993;Kendrick et al, 1996), and Tau (Shibanoki et al, 1993). Also, intrastriatal infusion of cr-amino-3-hydroxy-5-methylisoxazole-4-propionate (AMPA)/kainate-receptor agonists increases extracellular DA (Keefe et al, 1993;Kendrick et al, 1996;Smolders et al, 1996), GABA (Bianchi et al, 1994(Bianchi et al, , 1996Kendrick et al, 1996), and Tau (Bianchi et al, 1996).…”
mentioning
confidence: 99%
“…In striatum, local infusion of the Glu agonist N-methyl-D-aspartate (NMDA) increases extracellular DA (Keefe et al, 1992;Moran et al, 1993;Kendrick et al, 1996), GABA (Moran et al, 1993;Young and Bradford, 1993;Kendrick et al, 1996), and Tau (Shibanoki et al, 1993). Also, intrastriatal infusion of cr-amino-3-hydroxy-5-methylisoxazole-4-propionate (AMPA)/kainate-receptor agonists increases extracellular DA (Keefe et al, 1993;Kendrick et al, 1996;Smolders et al, 1996), GABA (Bianchi et al, 1994(Bianchi et al, , 1996Kendrick et al, 1996), and Tau (Bianchi et al, 1996).…”
mentioning
confidence: 99%
“…It has been shown that glutamatergic activation induces CaZ+-dependent and CaZ+-independent release of [3H] GABA from cultured neurons from striatum (Pin and Bockaert, 1989;Weiss, 1988) hippocampus (Harris and Miller, 1989) and cortex (Drejer and Honore, 1987). Recently, Young and Bradford reported that a NMDA stimulated [14C]GABA release from rat striatum in an in vivo microdialysis paradigm (Young and Bradford, 1993). Each of the experiments cited above were carried out in the presence of a GABA transaminase inhibitor that was included to protect the labelled GABA from metabolism during loading.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that administration of 5-HI antagonists may be effective in the treatment of Huntington's disease patients. It has been proposed (Young et al, 1988;Ruzicka and Jhamandas, 1991;Young and Bradford, 1993) that release of other transmitters, e.g., GABA, glutamate, and peptides, also occurs after administration of KA. This finding also suggests that these transmitter antagonists may be effective in this disease.…”
Section: Neurochemical Changes Predicted In Huntington's Diseasementioning
confidence: 99%